2007
DOI: 10.1002/anie.200604601
|View full text |Cite
|
Sign up to set email alerts
|

Template‐Directed Synthesis of a π‐Conjugated Porphyrin Nanoring

Abstract: Round the bend: Bending a molecular wire round an eight‐spoked template leads to the formation of a highly symmetric belt‐shaped π system (green in picture). Addition of a large excess of pyridine releases the corresponding cyclic octamer from the template.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
122
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(125 citation statements)
references
References 37 publications
(26 reference statements)
2
122
0
1
Order By: Relevance
“…We investigated the palladium-catalysed oxidative coupling of the linear zinc-porphyrin 10-mer l-P10 in the presence of hexa-pyridyl template T6 23,34 and octa-pyridyl template T8 35 ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated the palladium-catalysed oxidative coupling of the linear zinc-porphyrin 10-mer l-P10 in the presence of hexa-pyridyl template T6 23,34 and octa-pyridyl template T8 35 ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Expanded porphyrins have attracted considerable attention, in part because of their large conjugated p-system and flexible conformation leading to unique spectral, electrochemical and coordination properties , and in part they have wide potential applications in the fields of functional materials, molecular wires and near-infrared dyes [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Hexaphyrins are an example of expanded porphyrins which contain six pyrrole rings in the macrocycle and possess a sufficiently large porphyrin cavity to allow for the coordination of two metal ions and the formation of dinuclear metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work of Sanders and Anderson, [4] several CPOs in which the individual porphyrin rings are connected by covalent bonds have been reported. [5][6][7][8][9][10] CPOs have also been investigated in other fields such as host-guest chemistry and single molecule photochemistry. [7] We are interested in covalently linked arrays in which the bridging units are fully conjugated with the porphyrin π-system, including CPOs.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first conjugated diporphyrin system, a butadiyne-linked dimer, [11] was synthesised, many other porphyrin systems that offer strong electronic communication through their conjugated linkers have been investigated. The butadiyne and other linkers have been studied extensively, with numerous papers reporting interesting results with potential in various fields, [7,10, including recently two-photon absorption [31,34,[37][38][39][40][41][42][43][44] and two-photon photodynamic therapy. [14,15,41,45] Anderson suggested that an azo linkage would provide the optimum degree of interporphyrin conjugation and be a good bridge for facilitating electronic communication between the porphyrins in the ground state.…”
Section: Introductionmentioning
confidence: 99%